PATHOMORPHOLOGICAL CHANGES IN CARDIAC MUSCLE IN CHRONIC KIDNEY DISEASE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Chronic kidney disease (CKD) is a progressive systemic disorder characterized by irreversible impairment of renal excretory, metabolic, and endocrine functions, leading to widespread structural and functional alterations in multiple organs. Among these, the cardiovascular system—particularly the myocardium—represents the most vulnerable target. Persistent uremic intoxication, arterial hypertension, anemia, electrolyte imbalance, and disturbances in calcium–phosphorus metabolism collectively contribute to profound myocardial remodeling. These pathological processes result in cardiomyocyte hypertrophy, interstitial fibrosis, microvascular damage, and progressive deterioration of myocardial contractility. The constellation of these alterations forms the morphological basis of uremic cardiomyopathy. This article analyzes the mechanisms, histopathological features, and clinical implications of myocardial pathomorphological changes associated with chronic kidney disease based on contemporary scientific literature.